A mixed-flow simulation model for congested intersections with high pedestrian–vehicle traffic flows. (May 2014) - Zhang, Xin; Chang, Gang-Len
In design of plans for major metropolitan areas, it should be recognized that a potentially large percentage of the population is walking instead of driving. The massive number of pedestrians may cause tremendous burden to vehicles in the roadway network, and thus should be adequately accommodated. However, limited research has been done to qualitatively evaluate the effectiveness of different control plans at such mixed-flow intersections. Hence, the development of a simulation tool, capable of replicating the realistic road conditions for both the pedestrian and vehicle flows, is an imperative task. Such a simulation tool should be able to account for conflicts between pedestrians, between vehicles, and between pedestrians and vehicles. In this study, we attempt to address this vital subject with the mixed-cellular automata (MCA) method. Our proposed simulation model has integrated the strengths of the CA method with some probabilistic functions, offering a realistic mechanism to reflect the competing and conflict interactions between vehicle and pedestrian flows. To ensure the proposed model's applicability, this study has used field data to demonstrate the parameter calibration process and examples of some applications. Our extensive experimental results clearly indicate that the simulation model could realistically capture the behaviors and characteristics of mixed flows, offering an effective tool for potential real-world applications.